Postbaccalaureate Research Education Program (PREP) at Wake Forest University (WFU). - Gwathmey, Tanya; Diz, Debra (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
The Wake Forest PREP Scholars program (NIGMS R25 GM064249) targets undergraduate students from underrepresented minorities or disadvantaged backgrounds who are interested in working toward a PhD in the biomedical sciences. The program provides 1-2 years of intensive research experiences, career guidance, and GRE preparation. Like first-year graduate students, PREP students participate in a journal club and individualized coursework. We work closely with the Graduate School of Arts & Sciences and graduate program directors to place students in courses and professional development programs that will position them for entry into WFU or national PhD programs. The students choose their research mentors according to their research interests, and established scientists serve as career mentors based on the student's long-term professional development interests. A poster symposium held each June highlights trainee research projects. Between 2001 and 2015, 74 trainees participated; 95 percent remain in science-related careers; 25 percent (17) remained at WFU after completing the program. Most are African American (~75 percent) or Hispanic (18 percent). Career choices include entry into PhD 64 programs (63 percent), Master's programs (35 percent), professional schools (13 percent), math or science teaching or technical positions (15 percent), and retention in graduate and professional schools exceeds 90 percent (total over 100 percent as multiple categories apply). PREP trainees represent ~25 percent of the minority students in WFU biomedical science graduate programs, and since PREP started, the percentage of underrepresented minority students in these programs has nearly tripled from a starting value of less than 5 percent. Sixteen students have completed the PhD, and three hold assistant professorships. The program has increased the success of underrepresented minorities, including the disadvantaged, in WFU and national PhD programs in the biomedical sciences.